2019
DOI: 10.9787/kjbs.2019.51.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of F2 Population Derived from the Cross Between Perilla Frutescens var. Frutescens and var. Crispa

Abstract: In this study, genetic analysis was conducted on the inheritance of qualitative traits, such as leaf color, flower color, seed size, and seed hardness, in the F2 population derived from the cross between var. frutescens and var. crispa. As determined by the separation pattern of each trait in the F2 population, F2 plants with a green color were more common than those with a purple color on the leaf surface, whereas F2 plants with a purple color were more common than those with a green color on the reverse side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…frutescens could be an escaped form from cultivation, or otherwise likely derived from hybrids between accessions of the CWTPC. Although there is still no accurate report on the natural hybridization rate in the Perilla crop and its weedy varieties, recently Lim et al (2019, 2021) [ 17 , 18 ] and Kim et al (2021) [ 19 ] reported artificial hybridization between cultivated var. frutescens and weedy var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…frutescens could be an escaped form from cultivation, or otherwise likely derived from hybrids between accessions of the CWTPC. Although there is still no accurate report on the natural hybridization rate in the Perilla crop and its weedy varieties, recently Lim et al (2019, 2021) [ 17 , 18 ] and Kim et al (2021) [ 19 ] reported artificial hybridization between cultivated var. frutescens and weedy var.…”
Section: Discussionmentioning
confidence: 99%
“…The accessions of the CWTPC have the same number of chromosomes, 2n = 40 [ 13 ]. Additionally, cross experiments have been carried out by securing mating between accessions of the CWTPC using artificial pollination [ 14 , 15 , 16 , 17 , 18 , 19 ]. Therefore, it is important to understand the genetic variation and phylogenetic relationships between accessions of the CWTPC, and this will provide a rich source of information for making full use of germplasm resources in Perilla crop breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more than 500 seeds of the F 2 population are produced in F 1 plant. For this reason, genetic analysis of the entire F 2 population is not possible (Lim et al 2019). Therefore, in this study, some lines of the F 2 population were selected based on leaf characteristics such as leaf color (green or purple) and leaf shape (nonwrinkled or wrinkled) (see Fig.…”
Section: ; Mackay 2001mentioning
confidence: 99%
“…frutescens and var. crispa can be crossed with each other by arti cial pollination (Honda et al 1990(Honda et al , 1994Lim et al 2019). For example, Perilla frutescens var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation